(untitled) (Architecture Image Studies, 2025)
This study examined the relationship between financial literacy, information and communication technology (ICT) adoption, and the performance of household enterprises in Nigeria. Using data from the Global Findex 2021 survey, the analysis employed Logit and Two-Stage Least Squares (2SLS) instrumental variable regression models to explore how financial knowledge and digital tools influence the likelihood of establishing or expanding household businesses. Descriptive results reveal that only 37% of Nigerian firms operate as household enterprises, reflecting limited contribution to national output. Indicators of financial literacy remain low, with just 14% of households saving for retirement and 31% using debit cards, while ICT adoption is moderate, as 77% of households own mobile phones but only 6% make online payments. Empirical findings demonstrate that ICT adoption and financial literacy significantly and positively affect household enterprise participation, suggesting that access to digital finance and basic financial knowledge enhances entrepreneurial capacity. Workforce participation and respondents’ age also show significant effects, whereas income, education, and gender are not statistically significant. The 2SLS results further validate that financial literacy indicators, such as saving behaviour and use of digital financial services reinforce enterprise activity. Thus, underscoring the need for targeted interventions, including integrating financial education into school curricula, community training, and expanding ICT infrastructure to stimulate household-level entrepreneurship.